Tough nano adhesive and preparation method thereof
By combining emulsifier and pH value, combined with high-speed dispersion and ultrasonic technology, nanobonding agents with high toughness and strong neutron/γ-ray shielding ability were prepared, which solved the problems of large particle size, large amount of use and unstable performance of the adhesive. , expands the application field and reduces costs.
Patent Information
- Application Number
- CN202411309405.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
AI Technical Summary
The existing binders have large particle size, large amounts of use, unstable performance and low toughness, making them difficult to meet the electrochemical performance requirements of fine electronic products, and their application fields are limited.
By combining the HLB value and pH value of the emulsifier, combining high-speed dispersion and ultrasonic synergy technology, heavy metal alloy quantum dots are introduced to prepare epoxy resin nanoemulsion adhesives with nanoparticle sizes, and the curing agent ratio is formulated to improve particle size and strength. Nanoadhesives forming core-shell structures.
The prepared nanobonding agent has high toughness, excellent neutron/γ-ray shielding ability, small particle size, large bonding area, wide application range, low cost and easy to obtain, and after curing, it forms a three-dimensional pore structure. Viscoelastic.
Smart Images

Figure CN119144260A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, and in particular relates to a tough nano adhesive and a preparation method thereof. Background Art
[0002] With the development of economy and science, adhesives have become increasingly important. They are indispensable in industry, agriculture, transportation, medical treatment, national defense and people's daily life. Adhesives in my country started in the 1950s. After entering the 1990s, the adhesive industry has developed by leaps and bounds. Due to the outstanding advantages of adhesives, such as convenience, wide application field, energy saving and environmental protection, low cost and safety, adhesives have become an important type of fine chemical products and are indispensable materials in people's lives and modern industries. However, the current adhesives have large particle size, large dosage, unstable performance, and difficult to control particle size, so they cannot be well applied to the above fields; and they have low toughness, which is not conducive to the electrochemical performance of fine electronic products. Therefore, the development of tough nano adhesives is of great significance in expanding the application field of adhesives. Its increased adsorption surface area, enhanced bonding force and improved flexibility can be applied to more sophisticated electronic products, and the less amount is used, the more energy-saving and environmentally friendly.
[0003] Epoxy resins are of various types and widely used, and have many excellent properties that other resins do not have: (1) excellent chemical resistance, especially alkali resistance; (2) strong adhesion, especially to metals; (3) good heat resistance; (4) widely available. Epoxy adhesives are an important type of adhesives. Among them, TDE-85 epoxy resin is a trifunctional epoxy resin, which has the dual characteristics of alicyclic epoxy and glycidyl ester. It has a higher epoxy value, so its reactivity is greater than that of general alicyclic epoxy resins. The adhesive obtained after curing can be used in aviation, aerospace, nuclear power, electronics and other fields. There are many types of amine curing agents, such as polyetheramines. By selecting different types of polyetheramines, a series of properties such as reactivity, toughness, viscosity and hydrophilicity of polyetheramines can be adjusted, and the amine group provides the possibility for polyetheramines to react with a variety of compounds.
[0004] The above two raw materials are cheap, easy to obtain, and a wide variety of them are convenient for adjusting the characteristics of the reaction products. They have good mechanical properties and bonding strength and can react at low temperatures. The adhesive obtained after curing can be used in many fields such as aviation, aerospace, nuclear power, and electronics. After being prepared into nanoemulsions, the adsorption surface area is increased, the bonding ability is further enhanced, and the application field is further expanded to adhesives that can be used for battery materials. Summary of the invention
[0005] The invention aims at the deficiencies of the prior art for preparing tough nano adhesives and provides a tough nano adhesive and a preparation method thereof. The prepared epoxy resin nanoemulsion adhesive has high toughness, small particle size and excellent neutron / gamma ray shielding ability.
[0006] The invention obtains a stable emulsion with nanometer particle size by adjusting the HLB value of the emulsifier, adjusting the pH value, high-speed dispersion and ultrasonic coordination, and introducing heavy metal alloy quantum dots; and changes the particle size and strength of the nano adhesive by adjusting the ratio of the curing agent, and the adhesive has good toughness and excellent neutron / gamma ray shielding ability.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a tough nano adhesive, the method comprising:
[0009] S1. Preparation of dispersion: A mixture of an emulsifier, a dispersant, nano-boron carbide, graphene and a curing agent is uniformly dispersed in deionized water using a high-speed disperser at room temperature, and a pH buffer is added to obtain a functional curing agent dispersion having a certain pH value;
[0010] S2. Preparation of diluent: uniformly mixing the epoxy resin, heavy metal alloy quantum dots and the diluent by an auxiliary heat stirring method to obtain a functional epoxy resin diluent;
[0011] S3. Preparation of tough nanoemulsion: slowly and evenly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid at room temperature, and use high-speed stirring dispersion and ultrasonic synergistic method to achieve uniform dispersion. The epoxy resin in the dilution liquid is dispersed into nanospheres during the high-speed dispersion process of S3. The core-shell structure is prepared by adsorption and electrostatic assembly, and a high content of polyetheramine chain segments are chemically grafted on the surface to construct a super-hydrophilic surface structure, so that it can achieve ultra-fine particle size emulsification and long-term stability, and complete the synthesis of spherical nano-adhesives with a diameter of ≤10nm and self-toughness.
[0012] Furthermore, steps S1 and S2 include the following raw material compositions in weight percentage: 6.83%-7.65% hydrophilic emulsifier, 0.46%-0.51% lipophilic emulsifier, 0.34%-0.38% dispersant, 0.15%-0.17% nano boron carbide, 0.15%-0.17% graphene, 1.72%-12.15% curing agent, 75.49%-84.96% deionized water, 3.04%-3.40% epoxy resin, 0.03% heavy metal alloy quantum dots, and 0.91%-1.02% diluent.
[0013] Furthermore, in steps S1 and S2, the following three raw material compositions are included in weight percentage:
[0014] (1) The curing agent is polyetheramine D2000, the hydrophilic emulsifier is 6.83%, the lipophilic emulsifier is 0.46%, the dispersant is 0.34%, the nano boron carbide is 0.15%, the graphene is 0.15%, the curing agent is 12.15%, the deionized water is 75.94%, the epoxy resin is 3.04%, the heavy metal alloy quantum dots are 0.03%, and the diluent is 0.91%;
[0015] (2) The curing agent is polyetheramine D400, hydrophilic emulsifier 7.54%, lipophilic emulsifier 0.50%, dispersant 0.38%, nano boron carbide 0.17%, graphene 0.17%, curing agent 3.02%, deionized water 83.83%, epoxy resin 3.35%, heavy metal alloy quantum dots 0.03%, and diluent 1.01%;
[0016] (3) The curing agent is polyetheramine D230, hydrophilic emulsifier 7.65%, lipophilic emulsifier 0.51%, dispersant 0.38%, nano boron carbide 0.17%, graphene 0.17%, curing agent 31.70%, deionized water 84.97%, epoxy resin 3.40%, heavy metal alloy quantum dots 0.03%, and diluent 1.02%.
[0017] Furthermore, in step S1, the emulsifier is a hydrophilic emulsifier OP-10 and a lipophilic emulsifier Span-80; the dispersant is sodium dodecyl sulfate; the curing agent is one or more of polyetheramine D2000, polyetheramine D400 or polyetheramine D230; and the pH buffer is NH3·H2O-NH4Cl.
[0018] Furthermore, in step S1, the stirring speed of the high-speed dispersion is 2000 rpm, and the time is 5-10 min.
[0019] Furthermore, in step S2, the epoxy resin is 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester (TDE-85); the heavy metal alloy quantum dots are Pb-Cd-Ag alloy quantum dots, and the diluent is polypropylene glycol diglycidyl ether.
[0020] Furthermore, in step S2, the stirring speed is 100 rpm, the time is 5-10 min, and the temperature is 40°C.
[0021] Furthermore, in step S3, the dripping acceleration of the functional epoxy resin dilution liquid is 1 d / s.
[0022] Furthermore, in step S3, the speed of the high-speed stirring and dispersing is 3000-4000 rpm, and the time is 30-35 min; the ultrasonic irradiation time is 10-15 min, the power frequency is 10 KHz-15 KHz, the output power is 150 W-200 W, the ultrasonic treatment is an oil bath, and the ultrasound uses an ultrasonic processor with a titanium (Ti) tip.
[0023] A tough nano adhesive prepared by the above preparation method.
[0024] The beneficial effects of the present invention compared to the prior art are:
[0025] 1. The present invention adopts a one-step preparation method to form a core-shell structure. The preparation method is simple and does not require any complicated steps and reaction conditions.
[0026] 2. The raw materials TDE-85 epoxy resin and polyetheramine curing agent used in the method of the present invention are low-cost, easy to obtain and green and environmentally friendly. The obtained cured product forms a three-dimensional porous structure after curing and has viscoelasticity, which solves the problem of high hardness and low elasticity of other resins after curing. It also has excellent neutron / gamma ray shielding ability, and its superior performance expands the scope of application.
[0027] 3. The present invention can control the particle size by adjusting the HLB of the emulsion, adjusting the pH value, coordinating high-speed dispersion with ultrasound, adding heavy metal alloy quantum dots to introduce charges, and changing the proportion of the curing agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the microscopic reaction between TDE-85 and polyetheramine emulsion;
[0029] Figure 2 This is the particle size diagram of TDE-85 and D2000 emulsion;
[0030] Figure 3 It is the particle size diagram of TDE-85 and D400 emulsion;
[0031] Figure 4 It is the particle size diagram of TDE-85 and D230 emulsion;
[0032] Figure 5 It is the particle size diagram of TDE-85 and D2000+D400 emulsion;
[0033] Figure 6 It is the particle size diagram of TDE-85 and D2000+D230 emulsion;
[0034] Figure 7 It is the particle size diagram of TDE-85 and D400+D230 emulsion;
[0035] Figure 8This is the bonding strength diagram of TDE-85 after curing with various curing agents;
[0036] Fig. 9 This is a comparison chart of the viscoelasticity of Examples 1 to 6. DETAILED DESCRIPTION
[0037] The following text description and accompanying drawings are used to clearly and completely describe the technical solutions in the embodiments of the present invention. Figure 1 The microscopic reaction diagram of epoxy resin, curing agent and emulsifier in the emulsion is shown in the figure. The embodiments described in this patent are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The method of the present invention obtains a uniform emulsion with a minimum particle size of 10 nm by adjusting various factors that affect the particle size of the emulsion. The nano adhesive has excellent neutron / gamma ray shielding ability. At the same time, the adhesive also has the following advantages: the nano emulsion adhesive has good stability and does not show sedimentation behavior after being placed for 60 days; since a curing agent is added during the preparation process, the composite adhesive can be cured when heated to a specified temperature, and has excellent toughness after curing; the particle size of the adhesive is extremely small, so it can provide a larger bonding area, reduce the amount of adhesive used, and is more environmentally friendly.
[0039] Embodiment 1:
[0040] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0041] S1. 8 g of curing agent 1 polyetheramine D2000, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0042] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0043] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. The particle size diagram is as follows Figure 2 As shown, the average particle size can be as small as 50nm, showing a double peak.
[0044] Embodiment 2:
[0045] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0046] S1. 1.8 g of curing agent 2 polyetheramine D400, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0047] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0048] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. The particle size diagram is as follows Figure 3 As shown, the average particle size can be as small as 9.5 nm and presents a single peak.
[0049] Embodiment 3:
[0050] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0051] S1. 1 g of curing agent 1 polyetheramine D230, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0052] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0053] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. The particle size diagram is as follows Figure 4 As shown, the average particle size can be as small as 9 nm and presents a single peak.
[0054] Embodiment 4:
[0055] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0056] S1. 4 g of curing agent 1 polyetheramine D2000 and 0.9 g of curing agent 2 polyetheramine D400, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0057] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0058] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. Particle size diagram is as follows Figure 5 As shown, the average particle size can be as small as 20.2 nm, showing a double peak.
[0059] Embodiment 5:
[0060] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0061] S1. 4 g of curing agent 1 polyetheramine D2000 and 0.5 g of curing agent 3 polyetheramine D230, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0062] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0063] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. The particle size diagram is as follows Figure 6 As shown, the average particle size can be as small as 19.5 nm, showing a double peak.
[0064] Embodiment 6:
[0065] The present invention provides a method for preparing a nano-adhesive, comprising the following steps:
[0066] S1. 0.9 g of curing agent 2 polyetheramine D400 and 0.5 g of curing agent 3 polyetheramine D230, 0.225 g of sodium dodecyl sulfate SDS, 4.5 g of hydrophilic emulsifier OP-10, 0.3 g of lipophilic emulsifier Span-80, 0.1 g of nano-boron carbide, 0.1 g of graphene, and 50 g of deionized water were added to a 250 mL beaker, and uniformly dispersed at 2000 rpm in a high-speed disperser for 10 min, and the pH of the dispersion was adjusted to 8 using NH3·H2O-NH4Cl buffer to obtain a functional curing agent dispersion;
[0067] S2. 2 g TDE-85 epoxy resin and 0.02 g Pb-Cd-Ag alloy quantum dots were dispersed in 0.6 g diluent polypropylene glycol diglycidyl ether to obtain a functional epoxy resin diluent;
[0068] S3. Slowly and uniformly add the functional epoxy resin dilution liquid to the functional curing agent dispersion liquid, and use high-speed dispersion and ultrasonic synergy. The stirring speed of high-speed dispersion is 4000rmp, the time is 30min, the ultrasonic irradiation time is 15min, the power frequency is 15KHz, and the output power is 200W, and the nano adhesive can be obtained. The particle size diagram is as follows Figure 7 As shown, the average particle size can be as small as 9.4 nm and presents a single peak.
[0069] The bonding strength of the above six curing agents and epoxy resin after curing is as follows Figure 8 As shown in the figure, when a single curing agent is used, as the length of the curing agent chain segment decreases, the strength of the adhesive gradually increases, and the bonding strength of the adhesive cured with D230 is the highest at 11.86Mpa; the effect of using a composite curing agent is better than that of a single curing agent, and the bonding strength increases with the decrease of the curing agent chain segment. The curing effect of the composite curing agent D400+D230 is the best, and the bonding strength of the adhesive can reach 12.21Mpa.
[0070] The toughness of the above six curing agents after curing with epoxy resin is shown in the figure below. Fig. 9 As shown in the figure, as the length of the curing agent chain segment decreases, the toughness of the adhesive gradually increases, and the best toughness of the adhesive cured with D230 is 2461N; the use of a composite curing agent is better than a single curing agent, and the toughness increases with the decrease of the curing agent chain segment. The D400+D230 composite curing agent has the best curing effect, which can make the toughness of the adhesive reach 3438N.
Claims
1. A method for preparing a tough nano adhesive, characterized in that: The method is: S1. Preparation of dispersion: A mixture of an emulsifier, a dispersant, nano-boron carbide, graphene and a curing agent is uniformly dispersed in deionized water using a high-speed disperser at room temperature, and a pH buffer is added to obtain a functional curing agent dispersion having a certain pH value; S2. Preparation of diluent: uniformly mixing the epoxy resin, heavy metal alloy quantum dots and the diluent by an auxiliary heat stirring method to obtain a functional epoxy resin diluent; S3. Preparation of tough nanoemulsion: slowly and evenly add the functional epoxy resin dilution liquid into the functional curing agent dispersion liquid at room temperature, and use high-speed stirring dispersion and ultrasonic synergistic method to achieve uniform dispersion.
2. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In steps S1 and S2, the following raw materials are included in weight percentage: hydrophilic emulsifier 6.83%-7.65%, lipophilic emulsifier 0.46%-0.51%, dispersant 0.34%-0.38%, nano boron carbide 0.15%-0.17%, graphene 0.15%-0.17%, curing agent 1.72%-12.15%, deionized water 75.49%-84.96%, epoxy resin 3.04%-3.40%, heavy metal alloy quantum dots 0.03%, and diluent 0.91%-1.02%.
3. The method for preparing a tough nano adhesive according to claim 2, characterized in that: In steps S1 and S2, the following three raw material compositions are included in weight percentage: (1) The curing agent is polyetheramine D2000, the hydrophilic emulsifier is 6.83%, the lipophilic emulsifier is 0.46%, the dispersant is 0.34%, the nano boron carbide is 0.15%, the graphene is 0.15%, the curing agent is 12.15%, the deionized water is 75.94%, the epoxy resin is 3.04%, the heavy metal alloy quantum dots are 0.03%, and the diluent is 0.91%; (2) The curing agent is polyetheramine D400, hydrophilic emulsifier 7.54%, lipophilic emulsifier 0.50%, dispersant 0.38%, nano boron carbide 0.17%, graphene 0.17%, curing agent 3.02%, deionized water 83.83%, epoxy resin 3.35%, heavy metal alloy quantum dots 0.03%, and diluent 1.01%; (3) The curing agent is polyetheramine D230, hydrophilic emulsifier 7.65%, lipophilic emulsifier 0.51%, dispersant 0.38%, nano boron carbide 0.17%, graphene 0.17%, curing agent 31.70%, deionized water 84.97%, epoxy resin 3.40%, heavy metal alloy quantum dots 0.03%, and diluent 1.02%.
4. A method for preparing a tough nano adhesive according to claim 1 or 2, characterized in that: In step S1, the emulsifiers are hydrophilic emulsifier OP-10 and lipophilic emulsifier Span-80; the dispersant is sodium dodecyl sulfate; the curing agent is one or more of polyetheramine D2000, polyetheramine D400 or polyetheramine D230; and the pH buffer is NH3·H2O-NH4Cl.
5. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In step S1, the stirring speed of the high-speed dispersion is 2000 rpm, and the time is 5-10 minutes.
6. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In step S2, the epoxy resin is 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester (TDE-85); the heavy metal alloy quantum dots are Pb-Cd-Ag alloy quantum dots, and the diluent is polypropylene glycol diglycidyl ether.
7. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In step S2, the stirring speed is 100 rpm, the time is 5-10 min, and the temperature is 40°C.
8. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In step S3, the dripping acceleration of the functional epoxy resin diluent is 1 d / s.
9. The method for preparing a tough nano adhesive according to claim 1, characterized in that: In step S3, the speed of the high-speed stirring and dispersing is 3000-4000 rpm, and the time is 30-35 min; the ultrasonic irradiation time is 10-15 min, the power frequency is 10 KHz-15 KHz, the output power is 150 W-200 W, the ultrasonic treatment is an oil bath, and the ultrasound uses an ultrasonic processor with a titanium (Ti) tip.
10. A tough nano adhesive prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Quantum dot luminescence transparent casting glue composite material
CN101580628A
Epoxy resin composition for neutron shielding, and method for preparing same
CN103619949A
Special emulsifying agent of aqueous solid epoxy resin emulsion and preparation method of emulsion
CN103755966A
Room-temperature-curable epoxy pouring sealant used under temperature shock environment condition and production method of room-temperature-curable epoxy pouring sealant used under temperature shock environment condition
CN110437781A
Adhesive for OLED frame packaging and preparation and application methods thereof
CN112341969A
